Manajemen Madrasah Berbasis Digital Terhadap Mutu Lulusan di MAN Insan Cendekia Aceh Timur - Mardhiah, Ainol; Yusrianti, Susi; Barus, Jumat (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to analyze the impact of digital-based madrasa management on the quality of graduates at MAN Insan Cendekia Aceh Timur. The importance of applying technology in educational management to increase the efficiency and effectiveness of the educational process, which in turn affects the quality of graduates, is the main focus of this research. The study explores how digital-based madrasa management can enhance the quality of planning, organizing, implementation, and control within the school. A qualitative approach with descriptive analysis was used in this research. Data was collected through interviews, observations, and documentation involving the school principal, teachers, and administrative staff as key informants. The findings show that in planning, the use of technology helps in developing a more structured curriculum and learning plans. In organizing, digitalization facilitates communication and task distribution. In implementation, digital applications support more interactive and efficient learning. Meanwhile, control through digital systems allows real-time monitoring of student and teacher performance, which influences the improvement of graduate quality. This study concludes that digital-based management contributes significantly to the enhancement of graduate quality at MAN Insan Cendekia Aceh Timur.